Namadhij Min al-Fikr al-Mali fi al-Islam: Waraqah Ma’lumat Asasiyyah - Mustafa Dasuki Kasabah (TSAQAFAH, 2009)
The renaissance of Islam in various countries has become new phenomenon in the global economy. At the same time it also become the challenge for the Western capitalism and Eastern socialism. This resurrection together with revised ideology and economic system is considered as the strategic solution. Frankly, Islam is the religion which has brought back the core of economy to its position proportionally. In order to get concrete and clear idea on Islamic economy, here the writer presents five books written by Muslim scholars, classic as well as contemporary. The first is Kitab al-Amwal written by Abu Ubaid bin Salam, according to Khalil Harras this book is considered as the best and the most comprehensive book of Islamic economy. The second is Kitab Al-Ahkam al-Sultaniyyah written by Imam Mawardi. The third is Al-Fikr al-Mali written by Ibnu Khaldun, which has high scientific authority from other books, it is systematic as well as contextual. The fourth is al-Iradat al-‘Ammah li al-Daulah al-Islamiyyah fi Sadr al-Islam wa Tatbiqatuha al-Mu’asirah written by Monzer Kahf. The fifth is Al-Nafaqat al-‘Ammah fi Al-Islam: Dirasah Muqaranah written by Yusuf Ibrahim Yusuf. The first three authors are classics and the rest are contemporary.